Analisis Implikatur Percakapan pada Pedagang Jamu di Pasar Tradisional Prenduan, Madura - Albaburrahim Albaburrahim; Mochamad Arifin Alatas (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Implicature is an implied meaning of speech that is conveyed indirectly by the speaker to the speech partner. This study aims to describe the conversational implications of herbal medicine traders in Prenduan traditional markets, Madura. This research used a pragmatic theoretical approach (implicature) and a descriptive qualitative methodological approach. The data collection technique of this study used the technique of listening, taking notes, and recording. The data analysis technique classified conversational implicatures based on the pragmatic theory approach. The results of the data analysis indicated that there were conversational implicature in the conversations of herbal medicine traders in Prenduan traditional market. Conversational implicatures are used, namely: prohibition, approval, refuse, command, request, assure, complaint, and report.